Experimental modal analysis on Wira car chassis - Mohd Hafizi, Nor Izham (2007)
One of the problem exist in automobile industry is vibration on the chassis. Resonance exists when excitation forces coincide with one of the natural frequency of the structure. So it is important to study the dynamic characteristic of the structure. Dynamic characteristic can be determined using Experimental Modal Analysis (EMA) method or Modal Testing. Dynamic characteristic or modal parameters are divided into three which are natural frequency, damping factor and mode shape. Structure used for this project is wira car chassis. Used Proton Wira needs to be dismantled, the purpose of dismantling the Proton Wira is because the modal testing is performed only on the chassis structure. Two methods from modal testing is performed on the chassis, there are roving impact hammer test and shaker test. Data collected from the hammer and shaker test is converted and imported to M' Scope yES, then chassis is simulated. Result obtain from both methods, is compared on each axis (x, y and z axis). However there is a small discrepancy in terms of natural frequency, which the discrepancy does not exceed then 5%.